Penanganan Dampak Pandemi Covid-19 Desa Majalaya Berbasis Pembangunan Lingkungan dan Budaya Literasi - Muhammad Rizki Athari Nandira; Syifaa Izza Latifah; Alifah Siti Nurjanah; Subagja Subagja; Nawwal Nawwal; Muhammad Dafa Al Ghifary; Melani Laela Lestari; Safira Rahmadanti; Fitri Kamila; Pra Atmanti Eka Anggraini; Eva Rachmawati (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
The Covid-19 pandemic has an impact on several sectors in the community of Majalaya Village. A few people in Majalaya Village have experienced a decrease in income until they have lost their profession. This activity aims to increase people’s reading interest and literacy culture towards information, help people find alternatives to increase income, increase public understanding of the importance of protecting the environment and provide knowledge about flood disaster mitigation and mobilize people to cultivate plants in the yard. This activity was held on July 13, 2020 to August 25, 2020. The level of literacy of the people of Majalaya Village is still low. So that important information such as Covid-19 information is not always delivered well to the people of Majalaya Village, the lack of land makes the people of Majalaya Village do not want to cultivate crops, and environmental issues around garbage and flood disasters still often occur around the Majalaya Village area. However, the local government has been quite responsive in dealing with environmental issues in the form of the formation of Tangguh Bencana (Destana) Village by Bandung Regency government. Keywords: Covid-19, literacy culture, Majalaya Village, environment